1990
DOI: 10.1016/0035-9203(90)90103-l
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of infection of dogs and man in Nigeria by lyssaviruses (family Rhabdoviridae)

Abstract: A survey was conducted for serum neutralizing antibodies against 3 members of the Lyssavirus group (rabies, Lagos bat and Mokola viruses) in Nigerian dogs and humans. Of 463 unvaccinated dogs sampled, 142 (30.7%) had antibodies against rabies; 39.2% of the stray dogs were positive. Of 241 dogs tested, 17.4% had antibodies against Mokola virus and 5.8% against Lagos bat virus. 28.6% of human samples tested had antibodies against rabies and, of 158 human samples tested, 12 (7.5%) had antibodies against Mokola vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
0
20
0
2
Order By: Relevance
“…Aghomo et al [9] had reported the presence of rabies virus antibodies in over 15.93% of unvaccinated dogs in the southwestern part of Nigeria. Similarly, Ogunkoya et al [10] reported the presence of rabies antibodies in 30.7% and 28.6% of unvaccinated dogs and humans respectively in Nigeria. This present finding has therefore augmented the previous reports.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Aghomo et al [9] had reported the presence of rabies virus antibodies in over 15.93% of unvaccinated dogs in the southwestern part of Nigeria. Similarly, Ogunkoya et al [10] reported the presence of rabies antibodies in 30.7% and 28.6% of unvaccinated dogs and humans respectively in Nigeria. This present finding has therefore augmented the previous reports.…”
Section: Resultsmentioning
confidence: 84%
“…In about three decades ago, serological evidence of rabies virus antibodies has been reported in 15.93% of unvaccinated dogs in Southwestern Nigeria [9]. Furthermore rabies neutralizing antibodies have been reported in 28.7% of unvaccinated humans in Southwestern Nigeria [10]. About 10 million people receive postexposure treatments each year after being exposed to rabies-suspect animals [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, one may not exclude the possibility that this enhancement can be associated with polyspecific antibodies which are able to bind to a large range of antigens [17]. (ii) Subclinical infection by rabies virus may occur in field conditions in countries endemic for rabies boosting the subsequent post-vaccination immune responses [18][19][20][21]. Although, rabies endemicity can have various epidemiological consequences on viral transmission, subclinical infection is very poorly described in the literature and the extent to which it may enhance the residual immunity of dogs to rabies has yet to be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several workers reported brucellosis among herdsmen, butchers and meat sellers with prevalence rates ranging between 11.0 and 55.0% (Alausa and Awoseyi, 1976;Aworh et al, 2013;Adamu et al, 2015) despite the fact that this zoonosis can be prevented in animals through the use of Bruella S19 vaccine which is produced by NVRI, Vom, Nigeria and readily available for farmers. Human rabies cases have also been reported in Nigeria for more than 4 decades (Kemp et al, 1972;Ogunkoya et al, 1990;Abubakar and Bakari, 2012;Eke et al, 2015) despite the availability of anti-rabies vaccines for dogs which are the major source of human rabies in Nigeria. Transmission of NZDs in Nigeria can be curtailed through efficient zoonoses surveillance, vaccination of animals against neglected zoonoses like rabies, brucellosis and anthrax, veterinary inspection of meat and the regulation of importation of animals and their products.…”
Section: Promotion Of Human Healthmentioning
confidence: 99%